2021
DOI: 10.1021/acsami.0c22185
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Activated Cell Sorting Using Coiled-Coil Peptides: An Alternative Strategy for Isolating Cells with High Efficiency and Specificity

Abstract: Magnetic-activated cell sorting (MACS) is an affinity-based technique used to separate cells according to the presence of specific markers. Current MACS systems generally require an antigen to be expressed at the cell surface; these antigen-presenting cells subsequently interact with antibody-labeled magnetic particles, facilitating separation. Here, we present an alternative MACS method based on coiled-coil peptide interactions. We demonstrate that HeLa, CHO, and NIH3T3 cells can either incorporate a lipid-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Impaired proliferation of the stem cells (observation) led to a rapid decrease in DSC frequency and takeover of the remaining fibroblasts. It is known that magnetic particles can lead to adverse effects such as influencing cell phenotype, function [ 36 , 37 ], and viability [ 38 , 39 , 40 ]. This indicates that the DSCs might have been affected by the antibodies and RapidSpheres™, which they were still attached to.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired proliferation of the stem cells (observation) led to a rapid decrease in DSC frequency and takeover of the remaining fibroblasts. It is known that magnetic particles can lead to adverse effects such as influencing cell phenotype, function [ 36 , 37 ], and viability [ 38 , 39 , 40 ]. This indicates that the DSCs might have been affected by the antibodies and RapidSpheres™, which they were still attached to.…”
Section: Resultsmentioning
confidence: 99%
“…Several cell purification methods have been established to collect cells with specific characteristics. Typical methods are (i) magnetic-activated cell sorting (MACS) [ 44 , 45 , 46 ], (ii) fluorescence-activated cell sorting (FACS) [ 47 , 48 ], and (iii) cell selection by genetic editing with antibiotic resistance genes and antibiotic treatment (e.g., puromycin, neomycin, G418, and zeocin) [ 49 , 50 , 51 , 52 , 53 ]. In both the MACS and FACS methods, antibody binding on the targeting cells is essential, which indicates the possibility of antibody contamination on the final product of the specific cells, and antibody contamination in the final product is not desirable for clinical usage of the specific cells.…”
Section: Discussionmentioning
confidence: 99%
“…The lipopeptide-based fusion system CPE/CPK has already been used in many applications, such as cell sorting, liposome fusion, ,, liposome cell fusion, ,, lipid nanoparticle cell fusion, cell–cell fusion, and anion transporter delivery to membranes …”
Section: Fusogenic Peptidesmentioning
confidence: 99%
“…Besides receptor targeting, peptides can mediate the cellular uptake of functionalized lipid-based nanoparticles via a biomimetic mechanism using a coiled-coil interaction. Examples showed that they can be easily inserted into cells, liposomes, vesicles, and lipid nanoparticles (LNPs). ,, By modifying cells and vehicles, it could be shown that the uptake was drastically increased and selectivity over modified and nonmodified cells was achieved.…”
Section: Lipid-based Nanoparticles Functionalized With Fusogenic Pept...mentioning
confidence: 99%